Penggunaan Whatsapp dan Aktivitas Personal Bio-Poem Dalam Pembelajaran Grammar - Firda Febriana Azahra; Mirjam Anugerahwati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: Learning Grammar nowadays is still delivered by providing explanation and tasks only. This research aims to provide classroom intervention by using WhatsApp and Personal Bio-Poem activity in Intermediate Grammar Class, Universitas Brawijaya. The research method utilizes Classroom Action Research. To collect the data, classroom observation and document analysis were used. The result revealed that the implementation of Personal Bio-Poem activity has aligned with CLT learning model and Bloom’s Learning Domain Taxonomy. Besides the implementation of Personal Bio-Poem, it is also evident that the use of WhatsApp group can help students personalize their Grammar learning.Abstrak: Pembelajaran Grammar saat ini masih banyak disajikan dengan memberikan pemaparan dan latihan soal. Penelitian ini bertujuan untuk memberikan intervensi tindakan kelas menggunakan WhatsApp dan aktivitas Personal Bio-Poem dalam matakuliah Intermediate Grammar di Universitas Brawijaya. Penelitian ini menggunakan metode Penelitian Tindakan Kelas. Untuk mengumpulkan data, digunakan obervasi kelas dan analisis dokumen.  Hasil temuan menunjukkan penggunaan aktivitas Personal Bio-Poem memenuhi prinsip model pembelajaran CLT dan Bloom’s Learning Domain Taxonomy, sedangkan penggunaan aplikasi WhatsApp group terbukti dapat membantu peserta didik dalam mempersonalisasi pembelajaran Grammar.